The association between ethnicity, socioeconomic deprivation and receipt of hospital-based palliative care for people with Covid-19: A dual centre service evaluation. (September 2021) - Bajwah, Sabrina; Edmonds, Polly; Yorganci, Emel; Chester, Rosemary; Russell, Kirsty; Lovell, Natasha; Marsh, Lynne; Sleeman, Katherine E
Background: People from ethnic minority groups and deprived socioeconomic backgrounds have worse outcomes from COVID-19. Aim: To examine associations between ethnicity and deprivation with timing of palliative care referral for inpatients with COVID-19. Design: Service evaluation of consecutive patients with COVID-19 referred to palliative care. Sociodemographic (including age, sex, Index of Multiple Deprivation, ethnicity coded as White/non-White) and clinical variables were described. The primary outcome was timing of referral to palliative care. Associations between ethnicity and socioeconomic deprivation with the primary outcome were explored using multivariable regression. Setting/participants: Patients with COVID-19 referred to a hospital palliative care service across two London hospitals February–May 2020. Results: A total of 334 patients were included. 119 (36%) were from a non-White ethnic group; most commonly Black British (77, 23%) and Asian British (26, 8%). A longer time between admission and palliative care referral was associated with male gender (IRR 1.23, 95% CI 1.14–1.34) and lower levels of socioeconomic deprivation (IRR 1.61, 95% CI 1.36–1.90) but not ethnicity (IRR = 0.96, 95% CI 0.87–1.06). Conclusions: This large service evaluation showed no evidence that patients from ethnic minority or more deprived socioeconomic groups had longer time to palliative care referral. Ongoing data monitoring is essential for equitable service delivery.